The effect of a cashew bark decoction on the healing of induced oral ulcers in guinea pigs - Regudo, Ma. Margarita; Quia, Rita Carmen S.; Vergel de Dios, Nanette (Adviser).
The paper aims to determine the effect of a cashew bark decoction on the healing process of induced oral ulcers in guinea pigs. Ulcers were induced on the right and left sides of the inner mucosa of the lower lips of 10 guinea pigs using a ball tip attached to an electrosurgical unit. Ulcers on the right side represented the experimental group while those on the left represented the control group. The first phase of experiment served to determine the healing times of ulcers from both groups. The decoction was applied 2 times a day to the experimental group. Changes in appearance was recorded on a daily basis until complete healing took place. Procedures done in the first phase was repeated in the second phase. One guinea pig was sacrificed every 3 days for histologic study. Based on clinical observations, there was no difference in the appearances of ulcers from the two groups. Although healing occured earlier in the experimental group, the difference in the average number of healing days between the two groups was too small a value for it to be significant.
Seminar Paper--Doctor of Dental Medicine Medicine--University of the Philippines Manila.
Keywords: Cashew -- Therapeutic use